2022
DOI: 10.46729/ijstm.v3i1.452
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Auditor's Ability to Detect Fraud: Internal and External Factors

Abstract: Fraud cases that occur in Indonesia have fluctuated every year and in 2020 the number of state losses due to fraud is the largest in the last five years. The purpose of this study was to determine the effect of internal factors (experience and professional skepticism) and external (whistleblowing and time budget pressure) on the ability of auditors to detect fraud. Sampling using a survey method in the form of a questionnaire given to respondents, namely internal auditors the inspectorate and produced as many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
1
6
1
1
Order By: Relevance
“…It can be concluded that the exogenous variable of auditor experience does not have a positive effect on the endogenous variable of the auditor's ability to detect fraud, because it is not significant which means H3 is not accepted or rejected. This research is not in line with previous research (Cortinah & Ruslim, 2022;Iskandar et al, 2022;Joko, 2023;Putri et al, 2022;Rahmawati & Kuntadi, 2022;Wahidahwati & Asyik, 2022).…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…It can be concluded that the exogenous variable of auditor experience does not have a positive effect on the endogenous variable of the auditor's ability to detect fraud, because it is not significant which means H3 is not accepted or rejected. This research is not in line with previous research (Cortinah & Ruslim, 2022;Iskandar et al, 2022;Joko, 2023;Putri et al, 2022;Rahmawati & Kuntadi, 2022;Wahidahwati & Asyik, 2022).…”
Section: Discussioncontrasting
confidence: 98%
“…Professionalism has a positive effect on the auditor's ability to detect fraud Cortinah (2022) and Iskandar (2022) explain that audit experience is a factor from within a person that can only be developed by the individual through the number of assignments carried out which can affect the auditor's ability to detect fraud. The higher the tenure of an internal auditor, the higher the work experience he has.…”
Section: H2mentioning
confidence: 99%
See 2 more Smart Citations
“…The attitude of independence is one of the important things in the success of detecting fraud and improving the ability of auditors. The attitude of independence needs to be owned by the auditor because it can be free from pressure and the interests of any party so that the auditor can detect whether or not fraud is present in the agency he has audited and if fraud is detected, the auditor is not involved in securing the practice of fraud (Iskandar et al, 2022).…”
Section: Hypothesis Developmentmentioning
confidence: 99%